Holocene Spatiotemporal Redox Variations in the Southern Baltic Sea - Hardisty, Dalton S.; Riedinger, Natascha; Planavsky, Noah J.; Asael, Dan; Bates, Steven M.; Lyons, Timothy W. (Frontiers in Earth Science, 2021)
Low oxygen conditions in the modern Baltic Sea are exacerbated by human activities; however, anoxic conditions also prevailed naturally over the Holocene. Few studies have characterized the specific paleoredox conditions (manganous, ferruginous, euxinic) and their frequency in southern Baltic sub-basins during these ancient events. Here, we apply a suite of isotope systems (Fe, Mo, S) and associated elemental proxies (e.g., Fe speciation, Mn) to specifically define water column redox regimes through the Baltic Holocene in a sill-proximal to sill-distal transect (Lille Belt, Bornholm Basin, Landsort Deep) using samples collected during the Integrated Ocean Drilling Program Expedition 347. At the sill-proximal Lille Belt, there is evidence for anoxic manganous/ferruginous conditions for most of the cored interval following the transition from the Ancylus Lake to Littorina Sea but with no clear excursion to more reducing or euxinic conditions associated with the Holocene Thermal Maximum (HTM) or Medieval Climate Anomaly (MCA) events. At the sill-distal southern sub-basin, Bornholm Basin, a combination of Fe speciation, pore water Fe, and solid phase Mo concentration and isotope data point to manganous/ferruginous conditions during the Ancylus Lake-to-Littorina Sea transition and HTM but with only brief excursions to intermittently or weakly euxinic conditions during this interval. At the western Baltic Proper sub-basin, Landsort Deep, new Fe and S isotope data bolster previous Mo isotope records and Fe speciation evidence for two distinct anoxic periods but also suggest that sulfide accumulation beyond transient levels was largely restricted to the sediment-water interface. Ultimately, the combined data from all three locations indicate that Fe enrichments typically indicative of euxinia may be best explained by Fe deposition as oxides following events likely analogous to the periodic incursions oxygenated North Sea observed today, with subsequent pyrite formation in sulfidic pore waters. Additionally, the Mo isotope data from multiple Baltic Sea southern basins argue against restricted and widespread euxinic conditions, as has been demonstrated in the Baltic Proper and Bothnian Sea during the HTM or MCA. Instead, similar to today, each past Baltic anoxic event is characterized by redox conditions that become progressively more reducing with increasing distance from the sill.